Full-scale test and simulation of a PBL anchorage system for suspension bridges. Issue 3 (3rd March 2020) - Li, Zhixiang; Zhao, Canhui; Shu, Yang; Deng, Kailai; Cui, Bing; Su, Yukun
Abstract: In suspension bridges, cable anchorage system is the critical structure for cable tension transmission. For traditional rear anchor girder anchorage system and pre-stressed anchorage system, problems such as local compression and inconvenient construction are inevitable. This paper presents the development of a novel PBL anchorage system used in the 4th Nanjing Yangtze River Bridge. This PBL anchorage system adopted grouped perfobond rib shear connectors (known as PBL shear connectors) in the independent perforated steel plate. Two full-scale specimens were extracted from the practical design. The load–slip curves and the strain developments were obtained. The results revealed the reliable load-carrying capacity and very slight residual slip after the cyclic unloading from the design load. The load carried by each row of PBL shear connectors proved the distributed load-carrying capacity. Finite-element analyses were conducted in ANSYS, which agreed well with the test results. Further parametric analyses focusing on the spacing and rows of PBL shear connectors were conducted. Based on the analysis results, the design methods of the PBL anchorage system were suggested.